Direct Optical Tuning of the Terahertz Plasmonic Response of InSb Subwavelength Gratings. Issue 2 (6th February 2013) - Deng, Liyuan; Teng, Jinghua; Liu, Hongwei; Wu, Qing Yang; Tang, Jie; Zhang, Xinhai; Maier, Stefan A.; Lim, Kim Peng; Ngo, Chun Yong; Yoon, Soon Fatt; Chua, Soo Jin
<x xml:space="preserve">Abstract</x> Direct optical tuning of the THz plasmonic response of InSb subwavelength gratings is demonstrated experimentally. By injecting carriers into the semiconductor plasmonic material optically, the resonant frequency of the grating structure blue shifts, leading to tuning of the THz transmission. Potential modulation speeds up to the GHz regime are characterized by carrier lifetime studies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>